UNDANG-UNDANG NO. 21 TAHUN 2008 SEBAGAI SARANA REKAYASA SOSIAL DALAM PENYELESAIAN SENGKETA EKONOMI SYARIAH (Universitas Islam Negeri Antasari Banjarmasin, 2014)
This paper is about Law No. 21 of 2008 about Islamic banking as social engineering through: Verse (1) On Religious Courts as a dispute resolution of Islamic economics, Law becomes a tool to change the society. Before the emergence of that Law, the parties resolve the dispute with Islamic banks through other institutions. With that role, the Religious Courts are located as social engineering as